The Mediating Role of Internet Addiction in the Relationship Between Self-Control and Aggression in Individuals with Anxiety Disorders - Morshedi, Maryam; Mohamadi, Akbar (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study was to examine the mediating role of internet addiction in the relationship between self-control and aggression among individuals diagnosed with anxiety disorders. Methodology: This cross-sectional study involved 220 individuals diagnosed with anxiety disorders, selected through purposive convenience sampling from psychiatric clinics in Tehran in 2023. The primary data were collected using three standardized questionnaires: Young's Internet Addiction Questionnaire (2009), Buss and Perry's Aggression Questionnaire (1992), and Tangney's Self-Control Scale (2004). The data were analyzed using structural equation modeling (SEM) via AMOS software version 23 to assess the direct and indirect effects of self-control on aggression, with internet addiction as the mediator. Findings: The results indicated a significant negative direct effect of self-control on aggression (β = -0.22, p = 0.008) and on internet addiction (β = -0.29, p = 0.001). Additionally, a significant positive direct effect of internet addiction on aggression was observed (β = 0.46, p = 0.001). The mediation analysis confirmed that internet addiction significantly mediated the relationship between self-control and aggression, indicating that individuals with lower self-control were more likely to develop internet addiction, which in turn increased their levels of aggression. Conclusion: The findings suggest that internet addiction plays a crucial mediating role in the relationship between self-control and aggression in individuals with anxiety disorders. Interventions targeting internet addiction and enhancing self-control may be effective strategies for reducing aggression in this population. These results underscore the importance of a holistic approach in treating anxiety disorders, addressing both self-regulatory capacities and maladaptive coping mechanisms.